The new norms and students’ motivation in the pandemic sphere / Nurul Aisyah Awanis A Rahim ... [et al.] - A Rahim, Nurul Aisyah Awanis; Wan Ab. Razak, Wan Maziah; Mohd Anuar, Ahmad Ismail; A. Rahim, Nurul Aisyah Munirah (Universiti Teknologi MARA, Perlis, 2021)
The global pandemic COVID-19 has hit the world tremendously and shifted all normal daily routines to a new way of living. Education and knowledge sharing has now been held virtually to prevent the spread of this life-threatening virus. Hence, students nowadays have to cope with so many changes in the execution of their courses and assignments. Aside from this challenge, lectures now have to be conducted strictly online and the lecturers can no longer physically be with them to teach face-to-face as per previous practice. Therefore, this study aims to explain the motivational conditions of students when using various media in ODL. The survey has been distributed to 174 numbers of students from one of the Higher Learning Institutions in East Peninsular Malaysia. The result showed that even students who are in worry, restless and wanted everything to be ended immediately, still try their best to perform and to gain knowledge through any medium that they can to perform their best.